2015
DOI: 10.1634/theoncologist.2014-0198
|View full text |Cite
|
Sign up to set email alerts
|

In the Era of Genomics, Should Tumor Size Be Reconsidered as a Criterion for Neoadjuvant Chemotherapy?

Abstract: Background. The Oncotype DX recurrence score (RS) assay has been validated for prediction of 10-year risk of distant recurrence and likelihood of benefit from chemotherapy in patients with estrogen receptor (ER)-positive, HER2-negative early breastcancer. Patients with high RS tumors have substantial benefit, and patients with low RS tumors have minimal if any benefit from chemotherapy. Tumor size is used as a key parameter when selecting patients for neoadjuvant chemotherapy. The aim of this study was to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 27 publications
1
5
1
Order By: Relevance
“…The TransNEOS findings complement those of previous studies suggesting that the Recurrence Score test may help guide decisions about neoadjuvant chemotherapy [27–33]. In the Pivot and Yardley studies of neoadjuvant chemotherapy, the rate of pathologic CR was 26% ( p = 0.02) and 30% ( p = 0.002), respectively, among patients with RS ≥ 31 but 0% among patients with RS < 18 [30, 31]. Recently, Bear and colleagues assessed the feasibility of using Recurrence Score results to guide neoadjuvant systemic therapy [27].…”
Section: Discussionsupporting
confidence: 76%
“…The TransNEOS findings complement those of previous studies suggesting that the Recurrence Score test may help guide decisions about neoadjuvant chemotherapy [27–33]. In the Pivot and Yardley studies of neoadjuvant chemotherapy, the rate of pathologic CR was 26% ( p = 0.02) and 30% ( p = 0.002), respectively, among patients with RS ≥ 31 but 0% among patients with RS < 18 [30, 31]. Recently, Bear and colleagues assessed the feasibility of using Recurrence Score results to guide neoadjuvant systemic therapy [27].…”
Section: Discussionsupporting
confidence: 76%
“…Although two reports showed there was no statistically significant association between tumor response and RS (26,27), some studies support the correlation between RS and tumor response to neoadjuvant systemic therapy (28)(29)(30)(31)(32)(33)(34). In univariate analyses of predictive factors for the ≥50%TR achievement from our study (Table 7), none of the models were statistically significant.…”
Section: Correlation Between Ms and Rscontrasting
confidence: 63%
“…RS has been proposed to also select HR+ HER2-BC patients who will benefit from NCT. The correlation between multi-gene assays such as Oncotype DX® RS from pretreatment biopsy tissue and tumor response to neoadjuvant therapy has been studied previously (26)(27)(28)(29)(30)(31)(32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note the concordance of low pathological response found in both studies in patients with lower Recurrence Score results (RS 0–25), suggesting these patients will not benefit from NAC despite having clinical criteria of NAC. Pivot el al [ 29 ] showed a similar effect in patients selected for NAC primarily based on large tumor size, in that patients with low RS results, with minimal if any expected long-term clinical benefit to NAC, were unlikely to achieve pCR.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there have been multiple small studies incorporating the Oncotype DX® test in the neoadjuvant setting. These studies have shown that pCR or clinical complete response (cCR) to chemotherapy almost never occurs in patients with a low Recurrence Score result by Oncotype DX [ [10] , [11] , [12] , [13] ]. Using other genomic signatures in the NAC setting, very few or no pathological responses were observed among patients with a low risk of recurrence (ROR) based on the PAM50 [ 14 ].…”
Section: Introductionmentioning
confidence: 99%